The Indigenous Concept of Vivir Bien in the Bolivian Legal Field: A Decolonial Proposal - Dolhare, María Itatí; Rojas-Lizana, Sol (The Australian Journal of Indigenous Education, 2017)
This article discusses the concept of Vivir Bien (Living Well) (VB) and its role as a decolonising project in connection with the Political Constitution of the Plurinational State of Bolivia (2009) (BC) and subordinated legislation. This subordinated legislation was enacted to implement in a more specific manner the general legal principles contained within the BC. The paper uses these legal texts within the framework of decolonial thinking to prove that the adoption of the concept of VB represents a legal and an epistemological shift that radically contests the dominant Western paradigm of modernity/coloniality. This shift has many facets; however, this article concentrates on two of them in order to characterise its radicalism: (a) the constitutional acknowledgment of the colonial difference, which is understood here as the pervading and living legacy of European colonialism in social organisations and the production of knowledge, and (b) the constitutional and legislative requirement of engaging in an ongoing intercultural dialogue as a vehicle for the achievement of a society based on the concept of VB. This article concludes that the confluence of these two facets marks the epistemological shift and is important in the advancement of the intercultural and decolonising project represented by the concept of VB.